Albumin-based nanocarriers loaded with novel Zn(II)-thiosemicarbazone compounds chart a new path for precision breast cancer therapy - Erdem-Kuruca, Serap; Ülküseven, Bahri; Erdemir Cilasun, Gökçe; Kariper, İshak Afşin; Özerkan, Dilşad; Danişman-Kalindemirtaş, Ferdane (Ovid Technologies (Wolters Kluwer Health), 2025)
This study explores the therapeutic potential of albumin-bound Zn(II)-thiosemicarbazone compounds (Alb-ZnTcA, Alb-ZnTcB) against breast cancer cells. Previous research indicates that these compounds hinder cancer cell proliferation by blocking DNA synthesis, promoting oxidative stress to induce apoptosis, and disrupting the cell cycle to inhibit cellular division. This study focuses on the loading and characterization of these potentially chemically unstable compounds on bovine serum albumin-based nanocarriers. Accordingly, unlike previous studies using albumin nanoparticles, in this study, ultraviolet light was used to precisely bind the therapeutic agent to albumin during the integration of thiosemicarbazones, achieving controlled nanoparticle size to control nanoparticle size. The mean diameter of Alb-ZnTcA nanoparticles was 32 nm, while Alb-ZnTcB exhibited an average diameter of 43 nm. Notably, Alb-ZnTcA displayed the highest cytotoxicity toward breast cancer cells, suggesting an optimal size for cellular uptake. Additionally, albumin-bound compounds showed enhanced cytotoxicity at lower concentrations, potentially minimizing adverse side effects. Apoptosis analysis indicated that both Alb-ZnTcA and Alb-ZnTcB induce cell death predominantly through apoptosis, effectively preventing the uncontrolled proliferation of cancer cells. These findings demonstrate the potential of Zn(II)-thiosemicarbazone compounds loaded on albumin-based nanocarriers for breast cancer treatment. The increased potency of Alb-ZnTcA and Alb-ZnTcB compared to free compounds, along with their ability to activate apoptotic signaling pathways in MCF-7 breast cancer cells, highlights a promising approach for future cancer therapies. This study suggests that albumin-bound Zn(II)-thiosemicarbazone compounds could offer a targeted and effective strategy in breast cancer treatment, leveraging the advantages of nanocarrier-based delivery systems.
Keywords: breast cancer treatment; thiosemicarbazones; zinc; nanoparticles; research & development; thiosemicarbazone-bovine serum albumin